Geochemical and Geological Characterization of Upper Permian Linghao Formation Shale in Nanpanjiang Basin, SW China - Gu, Yifan; Cai, Guangyin; Hu, Dongfeng; Wei, Zhihong; Liu, Ruobing; Han, Jing; Fan, Zhiwei; Hao, Jingyu; Jiang, Yuqiang (Frontiers in Earth Science, 2022)
The Upper Permian Linghao Formation shale is the most potential shale gas exploration target in Nanpanjiang Basin. In this study, X-ray diffraction, Field emission scanning electron microscopy, CH4 isothermal adsorption, and nuclear magnetic resonance cryoporometry are intergrated to reveal comprehensive characterization of Linghao Formation shale collected from studied well in Nanpanjiang Basin. Results indicate that organic-rich shales developed in the Ling 1 Member and the lower part of Ling 3 Member. The organic-rich shales are predominantly characterized by kerogen Type I, with a relatively high mature to over mature status. The Ling 1 organic-rich shale is mainly mixed shale lithofacies and the organic-rich shale in lower part of Ling 3 is mainly composed of argillaceous shale. The pore voulme in Ling 1 organic-rich shale is mainly contributed by 3 nm-6 nm and 8 nm-11 nm organic pores. The pore volume of Ling 3 organic-rich shale is mainly composed of 2nm-3nm and 4nm-11nm organic pores. The organic pores between 3nm and 10nm also have a small contribution to the pore volume. The absolute adsorption gas content of Ling 1 organic-rich shale are 1.21 m3/t and 1.64 m3/t, respectively. Absolute adsorption gas content of Ling 1 and Ling 3 organic-rich shale exceeds the minimum standard for commercial shale gas development in China (1.0 m3/t). According to the adsorption gas ratio of 50 %, the total gas content of Ling 1 and Ling 3 organic-rich shale can reach 3.28 m3/t and 2.28 m3/t, respectively. It is suggested that the Upper Permian Linghao Formation shale in the Nanpanjiang Basin has a significant potential for shale gas exploration.